2016
DOI: 10.1073/pnas.1514412113
|View full text |Cite
|
Sign up to set email alerts
|

SutA is a bacterial transcription factor expressed during slow growth inPseudomonas aeruginosa

Abstract: Microbial quiescence and slow growth are ubiquitous physiological states, but their study is complicated by low levels of metabolic activity. To address this issue, we used a time-selective proteomelabeling method [bioorthogonal noncanonical amino acid tagging (BONCAT)] to identify proteins synthesized preferentially, but at extremely low rates, under anaerobic survival conditions by the opportunistic pathogen Pseudomonas aeruginosa. One of these proteins is a transcriptional regulator that has no homology to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 70 publications
1
79
0
Order By: Relevance
“…Because we found that SutA cross‐linked most efficiently to E (Fig. and Supporting Information, Figs and ) and because our previous ChIP‐Seq results suggested that SutA could interact with either initiating or elongating RNAP in vivo (Babin et al , ), we focused on the interaction between SutA and E. First we used the homobifunctional reagent bis(sulfosuccinimidyl)suberate (BS 3 ), which cross‐links primary amines that are within about 25 Å of each other (Rappsilber, ). We added BS 3 to complexes formed with purified E and SutA (Supporting Information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because we found that SutA cross‐linked most efficiently to E (Fig. and Supporting Information, Figs and ) and because our previous ChIP‐Seq results suggested that SutA could interact with either initiating or elongating RNAP in vivo (Babin et al , ), we focused on the interaction between SutA and E. First we used the homobifunctional reagent bis(sulfosuccinimidyl)suberate (BS 3 ), which cross‐links primary amines that are within about 25 Å of each other (Rappsilber, ). We added BS 3 to complexes formed with purified E and SutA (Supporting Information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The precipitated protein was removed by centrifugation, and the concentration of liberated flavin was determined using the FAD extinction coefficient of ⑀ 450 ϭ 11,300 M Ϫ1 cm Ϫ1 . Proteomics-In-gel digests were performed as described previously (63), and LC-MS/MS analysis was performed at the Caltech Proteome Exploration Laboratory (64).…”
Section: Methodsmentioning
confidence: 99%
“…By performing a proteomic study of Pseudomonas aeruginosa to determine which proteins are actively being made under anaerobic survival conditions, she described the discovery of a small, acidic protein, SutA (survival under transitions), that is posttranscriptionally upregulated during slow growth. SutA associates with RNA polymerase and regulates the expression of genes required for ribosome biogenesis and others involved in biofilm development, secondary metabolite production, and fitness under fluctuating conditions (2). With this insight underscoring the importance of studying biofilm properties beyond the lab, the first session provided a basis for understanding processes involving the formation of biofilms and the dynamics of different naturally occurring biofilm communities.…”
Section: Biofilm Communities In Naturementioning
confidence: 99%